Detection of Jaguar (Panthera onca) From Genetic Material in Drinking Water - Wilcox, Taylor M.; Caragiulo, Anthony; Dysthe, Joseph C.; Franklin, Thomas W.; Mason, Daniel H.; McKelvey, Kevin S.; Zarn, Katherine E.; Schwartz, Michael K. (Frontiers in Ecology and Evolution, 2021)
Jaguar (Panthera onca) are of conservation concern and occur at very low densities in the northern portion of their range in northern Mexico and the southwestern United States. Environmental DNA sampling to detect genetic material from drinking water may be an effective approach for jaguar detection in these arid landscapes. Here we develop a qPCR assay for the detection of jaguar mitochondrial DNA, show that large quantities of DNA (mean 66,820 copies/liter) can be found in the drinking water of captive animals, and observe detectable levels of DNA (80 copies/liter) in a wild habitat with known jaguar populations. We suggest that environmental DNA sampling may represent a useful, complementary sampling tool for detection of rare jaguars, although effective application would require careful consideration of DNA persistence time in the environment.